Efficacy and toxicity of cladribine for the treatment of refractory acute myeloid leukemia: a meta-analysis - Zhou A; Han Q; Song H; Zi J; Ma J; Ge Z (Dove Medical Press, 2019)
Anqi Zhou, Qi Han, Huihui Song, Jie Zi, Jinlong Ma, Zheng GeDepartment of Hematology, Zhongda Hospital Southeast University, Institute of Hematology Southeast University, Nanjing 210009, People’s Republic of ChinaPurpose: To investigate the overall efficacy and toxicity of cladribine and cladribine-based chemotherapy in the treatment of patients with refractory acute myeloid leukemia (AML) based on meta-analysis.Methods: PubMed, EMBASE database, and the Cochrane Library were searched for relevant studies. Eligible studies were clinical trials of refractory AML assigned to cladribine with data on efficacy including complete remission (CR) rate, overall response rate (ORR) and overall survival. Toxicity was evaluated based on the early death rate and the incidence of grade 3 and 4 adverse events (AEs).Results: A total of 10 clinical trials including 422 refractory AML patients were analyzed. The overall CR rate was 42.2% (95% CI: 31.0–54.3%). And the ORR of seven trials including 235 patients was 49.7% (95% CI: 33.5–66.0%). The overall early death rate of 260 patients enrolled in five trials was 6.8% (95% CI: 4.3–10.6%). Thrombocytopenia, anemia, neutropenia, and infection were the most common grade 3 and 4 AEs.Conclusion: Cladribine is effective for refractory AML, and its efficacy can be increased with the combination of cladribine, cytarabine, and granulocyte-colony stimulating factor regimen.Keywords: cladribine, acute myeloid leukemia, refractory AML, meta-analysis